Economic growth and the labor markets: Europe's challenge - Charles Wyplosz (National Bank of Belgium, 2000)
This paper reviews the accumulated theory and evidence on the sources of European underperformance in terms of economic growth and unemployment. It takes the view that the main problem lies with labor market institutions, ranging from negotiation structures to hiring and firing costs, unemployment benefits, minimum wages and taxation. It adopts the view that undesirable labor market structures have interacted with adverse shocks. An important question concerns the reasons behind reluctance in some countries to undertake reforms. The paper's thesis is that such reforms are not Pareto improving: a majority of the population stands to lose while a minority would benefit. The largest countries, where co-operation does not come naturally, are particularly vulnerable to a no-reform outcome. This observation is next used to outline possible scenarios. The paper concludes with a discussion of what could be the ECB contributions to either make reforms more acceptable or to cope with a separation of Europe in two groups of countries, those which have managed to implement reforms and those that will continue to operate with a high rate of equilibrium unemployment.
Keywords: 330; Wirtschaftswachstum; Arbeitslosigkeit; Arbeitsmarktpolitik; EU-Staaten